Ins and outs of GPCR signaling in primary cilia - Schou, Kenneth Bødtker (EMBO Rep, 2015)
Primary cilia are specialized microtubule-based signaling organelles that convey extracellular signals into a cellular response in most vertebrate cell types. The physiological significance of primary cilia is underscored by the fact that defects in assembly or function of these organelles lead to a range of severe diseases and developmental disorders. In most cell types of the human body, signaling by primary cilia involves different G protein-coupled receptors (GPCRs), which transmit specific signals to the cell through G proteins to regulate diverse cellular and physiological events. Here, we provide an overview of GPCR signaling in primary cilia, with main focus on the rhodopsin-like (class A) and the smoothened/frizzled (class F) GPCRs. We describe how such receptors dynamically traffic into and out of the ciliary compartment and how they interact with other classes of ciliary GPCRs, such as class B receptors, to control ciliary function and various physiological and behavioral processes. Finally, we discuss future avenues for developing GPCR-targeted drug strategies for the treatment of ciliopathies.